Women and Underrepresented Minorities in Computing: A Historical and Social Study - Aspray, William (History of Computing, 2016)
This text examines in detail the issue of the underrepresentation of women, African Americans, American Indians, and Hispanics in the computing disciplines in the U.S. The work reviews the underlying causes, as well as the efforts of various nonprofit organizations to correct the situation, in order to both improve social equity and address the shortage of skilled workers in this area. Topics and features: presents a digest and historical overview of the relevant literature from a range of disciplines, including leading historical and social science sources; discusses the social and political factors that have affected the demographics of the workforce from the end of WWII to the present day; provides historical case studies on organizations that have sought to broaden participation in computing and the STEM disciplines; reviews the different approaches that have been applied to address underrepresentation, at the individual, system-wide, and pathway-focused level; profiles the colleges and universities that have been successful in opening up computer science or engineering to female students; describes the impact of individual change-agents as well as whole organizations.